Age-Related Metabolic Pathways Changes in Dental Follicles: A Pilot Study - Victor Coutinho Bastos; Victor Coutinho Bastos; Jéssica Gardone Vitório; Roberta Rayra Martins-Chaves; Flávia Leite-Lima; Yuri Abner Rocha Lebron; Victor Rezende Moreira; Filipe Fideles Duarte-Andrade; Thaís dos Santos Fontes Pereira; Lucilaine Valéria de Souza Santos; Liséte Celina Lange; Adriana Nori de Macedo; et al. (Frontiers Media S.A., 2021)
Aging is not a matter of choice; it is our fate. The "time-dependent functional decline that affects most living organisms" is coupled with several alterations in cellular processes, such as cell senescence, epigenetic alterations, genomic instability, stem cell exhaustion, among others. Age-related morphological changes in dental follicles have been investigated for decades, mainly motivated by the fact that cysts and tumors may arise in association with unerupted and/or impacted teeth. The more we understand the physiology of dental follicles, the more we are able to contextualize biological events that can be associated with the occurrence of odontogenic lesions, whose incidence increases with age. Thus, our objective was to assess age-related changes in metabolic pathways of dental follicles associated with unerupted/impacted mandibular third molars from young and adult individuals. For this purpose, a convenience sample of formalin-fixed paraffin-embedded (FFPE) dental follicles from young (<16 y.o., n = 13) and adult (>26 y.o., n = 7) individuals was selected. Samples were analyzed by high-performance liquid chromatography-mass spectrometry (HPLC-MS)-based untargeted metabolomics. Multivariate and univariate analyses were conducted, and the prediction of altered pathways was performed by mummichog and Gene Set Enrichment Analysis (GSEA) approaches. Dental follicles from young and older individuals showed differences in pathways related to C21-steroid hormone biosynthesis, bile acid biosynthesis, galactose metabolism, androgen and estrogen biosynthesis, starch and sucrose metabolism, and lipoate metabolism. We conclude that metabolic pathways differences related to aging were observed between dental follicles from young and adult individuals. Our findings support that similar to other human tissues, dental follicles associated with unerupted tooth show alterations at a metabolic level with aging, which can pave the way for further studies on oral pathology, oral biology, and physiology.